The Labour Mobility in the European Union: Economic and Social Determinants - Liana Son; Ioan Talpos; Ciprian Sipos (Theoretical and Applied Economics, 2008)
East and Central European countries are, most of them, migration countries for 18 years now and controversies on this subject are constantly emerging in the context of European Union enlargements. This paper aims to analyze some of the determinants of intra-European mobility and which are the interest destination countries for the migrant workers. The analysis is based upon a factorial model witch includes variables concerning the differential of labour cost and life and work conditions between European receiving and origin countries, in the decision of moving abroad.